The Influence of Attitudes, Subjective Norm, and Behavior Control on Individual Taxpayer Compliance with Moral Obligations as Moderation - Aidilla Winda Prastika; Sri Trisnaningsih (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the attitude of taxpayers, subjective norms, and behavioral control of taxpayer compliance moderated by moral obligations. This research method is a quantitative method with a descriptive approach. The results of the study show that the attitude of taxpayers has a significant effect on taxpayer compliance, and behavioral control has a significant negative effect on taxpayer compliance, while subjective norms have no significant effect on taxpayer compliance. In addition, moral obligation also strengthens the relationship between behavior control and taxpayer compliance, but weakens the relationship between behavior control and taxpayer compliance, and moral obligations are proven to be unable to moderate the relationship between subjective norms and taxpayer compliance.